2015
DOI: 10.1186/s12889-016-2701-1
|View full text |Cite
|
Sign up to set email alerts
|

One size does not fit all–qualitative process evaluation of the Healthy School Start parental support programme to prevent overweight and obesity among children in disadvantaged areas in Sweden

Abstract: BackgroundParental support interventions have shown some effectiveness in improving children’s dietary and physical activity habits and preventing overweight and obesity. To date, there is limited research on barriers and facilitators of school-based parental support interventions targeting overweight and obesity. This study aimed to describe barriers and facilitators influencing implementation of the Healthy School Start (HSS) intervention in disadvantaged areas in Stockholm, Sweden, from the perspective of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 32 publications
1
70
0
Order By: Relevance
“…Process evaluations are critical to understanding implementation success and the contextual factors that influence how an intervention works. However, on the basis of the pool of studies included in this review, process evaluations are rare: only 24% (n = 4) of included trials conducted a process evaluation . Three of these process evaluations assessed the issue of intervention fidelity, each concluding wide variance in implementation of the program across schools and settings.…”
Section: Discussionmentioning
confidence: 87%
“…Process evaluations are critical to understanding implementation success and the contextual factors that influence how an intervention works. However, on the basis of the pool of studies included in this review, process evaluations are rare: only 24% (n = 4) of included trials conducted a process evaluation . Three of these process evaluations assessed the issue of intervention fidelity, each concluding wide variance in implementation of the program across schools and settings.…”
Section: Discussionmentioning
confidence: 87%
“…It became clear that to create commitment among staff and implement the obesity prevention intervention with high fidelity, the staff should be offered training and opportunities to discuss the content of the programme. Our second trial showed that teachers' time for making the necessary preparations for the intervention and doing so before finalising their plans for the school year, influenced their engagement in the programme (Norman et al, 2016). Furthermore, the results of this study demonstrated that lack of parental engagement is a barrier to securing parental support.…”
mentioning
confidence: 68%
“…Our previous implementation study of HSS also supports this observation. Teachers who were told to carry out the programme felt they were being forced, which affected their engagement in the programme negatively (Norman, Nyberg, Elinder, & Berlin, 2016). To avoid opposition, staff should be actively involved in detailed planning regarding when and how the programme should be implemented.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The UK Medical Research Council's (MRC) framework for designing and evaluating complex interventions (programs) recommends process evaluations be undertaken as part of all randomised trials; as they describe important contextual factors, and can clarify causal mechanisms to aid interpretation of trial findings and explain variations in trial outcomes [16]. However, a recent systematic review of randomised controlled trials (RCTs) of schoolbased physical activity programs highlighted that process evaluations were rare, undertaken in just four of the 17 trials identified [11,[17][18][19][20]. Furthermore, none of the process evaluations described or assessed the delivery of implementation support strategies to facilitate implementation of the program [17][18][19][20], nor were process evaluation methods specified in a publically available protocol or register [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%